Accident Man : hitman's holiday [videorecording (DVD)] - Small, Stu; Adkins, Scott, 1976-; Adkins, Scott, 1976-; Stevenson, Ray, 1964-; Benson, Perry, 1961-; Chang, Sarah, 1985-; Fouracres, George; Mohammed, Faisal; Thomas, Peter Lee; Fowler, Beau; Long, Andy; Cinque, Flaminia; et al. (Samuel Goldwyn Films, 2023)
The Accident Man is back and this time he must beat the top assassins in the world to protect the ungrateful son of a mafia boss, save the life of his only friend, and rekindle his relationship with his maniacal father figure.